Challenges of Responsible Supply Chain Management - Szegedi, Krisztina; Kerekes, Károly Norbert (Theory, Methodology, Practice – Review of Business and Management, 2012)
Many firms are increasing their focus on their Supply Chain as a strategic factor. This focus has primarily emphasized cost reducing and risk minimizing, although some proactive companies began to manage their supply chain in a responsible way several years ago. This paper provides a comprehensive review of the part of the Corporate Social Responsibility literature that introduces responsibility to the field of supply chain management; furthermore, it processes public documents and Internet sites of major global firms suggesting a framework to implement RSCM practices. The aim of this article is the theoretical and practical foundation of potential research in the field of Responsible Supply Chain Management.